The Role of Ward Head Leadership in Developing the Competence of New Nurses - Retno Susanti (Indonesian Journal Publisher, 2025)
This study aims to identify and analyze the role of ward head leadership in shaping the competence of new nurses. The focus of the study is on how leadership strategies, training programs, and organizational support contribute to improving the clinical readiness and professionalism of new nurses. The research method used was qualitative with a descriptive approach through a literature study. Data collection techniques were carried out by reviewing relevant current scientific articles, while data analysis was conducted inductively through a process of theme identification, data reduction, concept categorization, and conclusion drawing. The results of the study show that effective ward head leadership—which integrates emotional, pedagogical, and strategic approaches—has a direct impact on strengthening the clinical competence, interpersonal skills, and work resilience of new nurses. The findings also reveal that leadership training based on authentic leadership, mindfulness, and 360-degree feedback significantly improves the managerial capacity of ward heads in mentoring new staff. The implications of these results emphasize the importance of integrating leadership development programs into the nursing management system and the need for institutional support in creating a sustainable learning environment. In conclusion, ward leadership is not only an administrative function but also a key agent in transforming the learning process and competency development in the clinical environment.